Fast‐mover advantages: Speed capabilities and entry into the emerging submarket of atlantic basin LNG - Hawk, Ashton; Pacheco‐De‐Almeida, Gonçalo; Yeung, Bernard (Strategic Management Journal, 2013)
Entry timing benefits and costs typically vary with firms' capabilities. In this study, we empirically examine the entry timing implications of firms' intrinsic speed capabilities, which refer to the ability to execute investment projects faster than competitors. We hypothesize that firms with intrinsic speed capabilities face low preemption risks and, thus, can afford to wait longer for uncertainty resolution before deciding to enter new markets. This hypothesis is more applicable when investment is associated with higher levels of commitment and, thus, greater option value of waiting. A direct implication is that late entrants with intrinsic speed capabilities should have greater expected post‐entry performance. We find support for these hypotheses in the Atlantic Basin liquefied natural gas ( LNG ) industry from 1996 to 2007 . Copyright © 2013 John Wiley & Sons, Ltd.